Implementasi Pedoman Perilaku Penyiaran Menurut Perspektif Komisi Penyiaran Indonesia (KPI) - Tulasi, Dominikus (Bina Nusantara University, 2014)
This multidiscipline research combines models and theoretical guidance of Indonesia Broadcasting Commission in implementing ethical behavioral guidance toward television broadcasting programs as mass media, a case study at Trans7. This qualitative research examined on how both Television management and Indonesia Broadcasting Commission highlight and perceive behavioral acting of host relating to entertainment programs. In one hand, program producer is able to construct, construe, and reconstruct societal opinions and mindset to its program. On the other hand, Indonesia Broadcasting Commission (KPI) construes the television program overacting and unethical. KPI judges the behavior of the program host does not deserve to present to the society referring to the broadcasting regulations, especially broadcasting behavioral guidance and broadcasting program standard (P3-SPS). Analyzing the implications television broadcasting program is a matter of negative image towards national culture and social norms through significant participant observation. This phenomenon is alarming, considering the host of TV programs which in the long run will be able to influence social value system and national culture. As it is able to gain an extensive understanding towards the identity makeup and sense of television broadcasting programs that exist within Indonesian society.